Pengaruh Hubungan Berkelanjutan terhadap Kesetiaan Nasabah di BMT NU Cabang Pragaan Kabupaten Sumenep - Achmad Tarmidzi Anas; Fadllan Fadllan (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2017)
One strategy for customers to survive and be even more loyal is to provide attractive product offerings, but that is not enough to get customers to survive and need other steps to retain customers, so that today there are many banks and non-bank financial institutions Which apply the concept of long-term relationship with customers. BMT NU Branch Pragaan Sumenep regency as a non-bank financial institutions that form a cooperative to build a sustainable relationship with customers, so it needs to be examined how the loyalty of its customers. The formulation of the problem in this study is whether the continuous relationship affects customer loyalty in BMT NU Branch Pragaan Sumenep regency? How big is the influence of ongoing relationship to customer loyalty in BMT NU Branch Pragaan Sumenep regency?. The purpose of this research is to know the influence of continuous relationship to customer loyalty in BMT NU Pragaan Branch of Sumenep regency, secondly to know how big influence continuous relationship to customer loyalty in BMT NU Branch Pragaan Sumenep Regency. This study uses a quantitative approach with the type of causal research and tools used simple linear regression analysis. The data used are primary data obtained through questionnaire. And Respondents are customers of BMT NU Branch Pragaan Sumenep with a population of 5005 customers and as many samples 98 customers with error rate of 10%. The results showed that there is a significant influence on the ongoing relationship to customer loyalty in BMT NU Branch Pragaan Sumenep. It is stated based on the result of Test-t yield correlation coefficient value tarithmetic= 14.325> ttable=1.290 with a significance level of 0.000 <0.1, and the value of positive beta coefficient. Of the coefficient of determination (R2) by using SPSS (Statistical for the Social Sciences) version 18, By looking at R square gain of 0.681. This means that 68.1% of customer loyalty is influenced by continuous relationships in BMT NU Branch Pragaan Sumenep. While the rest of 39.1% can be influenced by other factors. From the simple linear regression equation (Y = a+ bX) is Ŷ = 2.030 + 0.396X, where the constant value (a) of 2.030 indicates that if the continuous relationship variable is equal to zero (not taken into account), the customer's loyalty is 2.030 units and b = 0.396, it can be interpreted that the magnitude of customer loyalty variable coefficient marked positive (0,396) indicate that if continuous relationship increases 1%, hence loyalty score of customer will increase equal to 39,6%.